2020
DOI: 10.2217/cer-2020-0037
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing breast cancer awareness: a cross-sectional study in China

Abstract: Aim: This study aimed to explore the factors that influence breast cancer awareness. Materials & methods: A community-based cross-sectional study was conducted between January and April 2019 in Changchun, Jilin Province, China. Results: A total of 274 women were recruited for this cross-sectional study. Participants had a moderate level of breast cancer awareness (median = 76.50 [68.75, 84.00]). Women in the action/maintenance stages reported higher breast cancer awareness (p = 0.044). Women's bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…Those whose husbands attended primary school were less likely to be aware of breast cancer than those whose husbands attended tertiary school. This finding was supported by research findings from Turkey [ 19 ] and China [ 20 ]. This is most likely due to the fact that people with higher levels of education are more capable of obtaining more and effective information from various sources, as well as having the opportunity to communicate with their families about these specific health problems.…”
Section: Discussionsupporting
confidence: 80%
“…Those whose husbands attended primary school were less likely to be aware of breast cancer than those whose husbands attended tertiary school. This finding was supported by research findings from Turkey [ 19 ] and China [ 20 ]. This is most likely due to the fact that people with higher levels of education are more capable of obtaining more and effective information from various sources, as well as having the opportunity to communicate with their families about these specific health problems.…”
Section: Discussionsupporting
confidence: 80%
“…In accordance with the findings of previous studies, 10,11,19 multivariate regression analysis in this study identified several factors that influenced the level of breast cancer awareness among rural women in Southwest. Education level, breast disease history, and contraceptive use were found to be significant factors.…”
supporting
confidence: 90%
“…The overall awareness rate in the study population was 79.0%, with an average score of 73.0 (IQR, 66.0, 82.0), which is consistent with findings from other research conducted in China, where the moderate score was 76.50 (IQR, 68.75, 84.00). 11 , 24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A self-administered questionnaire was developed based on previous reports [20][21][22]. The questionnaire was composed of two parts.…”
Section: Study Instrumentmentioning
confidence: 99%